How does rapport impact knowledge transfer from older to younger employees? The moderating role of supportive climate - Rui, Hainan; Ju, Hailong (Frontiers in Psychology, 2022)
Introduction Knowledge transfer from older to younger employees plays a key role in lessening knowledge loss and maintaining firms' competitiveness. While the disharmony derived from a salient age difference between younger and older workers hinders such knowledge transfer. This study aims to construct a rapport model to address it. Methods Data from 318 respondents in various industries were collected through a questionnaire-based survey to test the proposed model. The research hypotheses were tested using hierarchical multiple regressions. Results Our empirical results show that almost all rapport dimensions facilitate such knowledge transfer; The moderating role of supportive climate is strong that it enhances or replaces the effects of rapport dimensions on such knowledge transfer. Discussion This study contributes to research on knowledge transfer and rapport by providing a detailed understanding of the relational mechanism of the knowledge transfer from older to younger employees based on a revised model of rapport. It also serves as a reference for firms to leverage rapport-building and a supportive climate to enhance this invaluable knowledge transfer.